HBR's 10 must reads on high performance - Sarris, William; Jania, Carolyn (Ascent Audio, 2022)
Set yourself on the path to greatness. If you read (or listen) to nothing else on performing at your highest level, listen to these ten articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you focus on what matters, manage your energy and attention, and achieve remarkable results. This book will inspire you to: - Improve on your weaknesses, not just your strengths - Identify what's holding you back - Rise above the pack - Take care of your physical health for sustained mental performance - Make small changes in your habits that lead to big results - Understand what motivates you - Use short-term goals to achieve long-term aspirations - Inspire others to reach their potential.
Online resource; title from title details screen (O'Reilly, viewed May 18, 2022)
Keywords: Work -- Psychological aspects; Performance; Success in business; Travail; Aspect psychologique; Succès dans les affaires; Work; Psychological aspects; Downloadable audio books; Audiobooks; Livres audio